Relationship between service quality and customer satisfaction in ferry transportation in Labuan - Wawasan Perdana Ferry / Stephanie John - John, Stephanie (2015)
Customer satisfaction has been subject of great interest to any organizations that involved in either sales or service industry. With maximizing profits and paired with minimal costs being the principal objectives of most organizations, customer satisfaction has become more and more important and a 'must have'. This is because through customer satisfactions sales can be increased, from satisfaction leads to customers' loyalty (Wilson et al., 2008. P79), recommendation and of course repeat purchase or use of service. This is what the management of Wawasan Perdana ferry trying to improve in order to achieve in providing their customer/passenger through good quality service. Nowadays, it is never enough just to have a product or a service offered to customers. Organizations are also obliged to provide more services in addition to what they are already providing. They are always the same common questions; Are the customers satisfied with our services? Are the services we provide to customer are up to the quality that our customers expected?